Losses of Radiation Belt Energetic Particles by Encounters With Four of the Inner Moons of Jupiter. Issue 2 (16th February 2022) - Long, Minyi; Ni, Binbin; Cao, Xing; Gu, Xudong; Kollmann, Peter; Luo, Qiong; Zhou, Ruoxian; Guo, Yingjie; Guo, Deyu; Shprits, Yuri Y.
Abstract: Based on an improved model of the moon absorption of Jovian radiation belt particles, we investigate quantitatively and comprehensively the absorption probabilities and particle lifetimes due to encounters with four of the inner moons of Jupiter (Amalthea, Thebe, Io, and Europa) inside L < 10. Our results demonstrate that the resultant average lifetimes of energetic protons and electrons vary dramatically between ∼0.1 days and well above 1, 000 days, showing a strong dependence on the particle equatorial pitch angle, kinetic energy and moon orbit. The average lifetimes of energetic protons and electrons against moon absorption are shortest for Io (i.e., ∼0.1–10 days) and longest for Thebe (i.e., up to thousands of days), with the lifetimes in between for Europa and Amalthea. Due to the diploe tilt angle absorption effect, the average lifetimes of energetic protons and electrons vary markedly below and above α e q α _eq = 67°. Overall, the average electron lifetimes exhibit weak pitch angle dependence, but the average proton lifetimes are strongly dependent on equatorial pitch angle. The average lifetimes of energetic protons decrease monotonically and substantially with the kinetic energy, but the average lifetimes of energetic electrons are roughly constant at energies <∼10 MeV, increase substantially around the Kepler velocities of the moons (∼10–50 MeV), and decrease quickly at even higher energies. Compared with the averaged electron lifetimes, the average proton lifetimes are longer at energies below a few MeV and shorter at energies above tens of MeV. Plain Language Summary: As a gaseous and giant planet, Jupiter has the largest magnetosphere in the solar system formed by the interaction between its internal magnetic field and the solar wind flows. Jovian radiation belts are regions of enhanced populations of energetic electrons and protons within its magnetosphere, with an intense and extreme radiation environment. An important feature is that various moons orbit around Jupiter within its magnetosphere, which creates chances for energetic particles to encounter moons, resulting in particle losses and modifying the spatial distributions of energetic particles and their energy spectra and pitch angle profiles. We improve an analytic model to evaluate particle lifetimes around the moon's orbits under the assumption that the moons are ideal insulators, though Europa has tenuous atmosphere and Io has ionosphere. We analyze particle absorption effects by encounters with some of the inner Jovian moons (Amalthea, Thebe, Io, and Europa) and give comprehensive analysis on energy and pitch angle dependences of energetic protons and electrons in Jovian radiation belts. Our improved quantifications of radiation belt particle loss due to moon absorption are suitable to be incorporated with other important physical processes to pursue understanding of the complex variability of the Jupiter's radiation belts. Key Points: The average lifetimes of energetic protons and electrons due to moon absorption vary dramatically from ∼0.1 to well above 1, 000 days Considering the moons as insulators, we find that the absorption of energetic protons and electrons by Io is the most intense Average proton lifetimes are longer than electron lifetimes at energies below a few MeV but shorter at energies above tens of MeV